Quando a leste vira centro: o desenvolvimento econômico da Zona Leste na perspectiva dos atores do Fórum para o Desenvolvimento da Zona Leste - Soares, Elizângela Teixeira (2016)
The East Zone of the city of São Paulo has been put in evidence on national and international news, with an increasing in 2010, when the district of Itaquera was chosen to host the opening of the World Cup soccer games 2014. The history of this region shows that it has been considered a commuter region, as it is opposed to the West Zone, the most developed zone of São Paulo and where the private and public investments are destined. Hosting the World Cup openings not only boosted roads, urban interventions, and the implementation of social facilities, but has also put in evidence again the struggle of the development of the East Zone. The present study was created in order to identify how the social characters of the region have organized on the face of such development process and how they have mobilized to take ownership of it. It was decided to start the study by the Forum for the East Zone Development (FDZL) and, from the network analysis methodology, questioning what kind of development are suitable for the region. The initial hypothesis stated that the Forum was articulating as a cohesive group, helping the development of the East Zone. However, the study showed that the Forum is a heterogeneous network, which on the moment of the competition for development was disjointed. The reorganization of the network intended to find the characters and identify exactly if it can demonstrate what I pointed out in relation to networks, that they are different players disputing for the same social space. The network shows that they do. Thus, the study revealed that the present conflict over the East Zone development is a dispute between organizations and social movements, such as the Forum organization, and what is on dispute is whether or not the East Zone will be constituted as a centrality